"I'm Not an Expert, But…": Perspectives on Aquatic Management for LGBTQ Participants. Issue 1 (April 2020) - Anderson, Austin Robert; Knee, Eric; Ramos, William Dominic
The purpose of this study was to examine the initiatives that current aquatic managers in campus recreation are implementing to create environments that are inclusive to lesbian, gay, bisexual, transgender, and queer (LGBTQ) participation and to assess the barriers to such initiatives. The study utilized in-depth semistructured interviews with nine campus recreation aquatic managers to examine steps that are currently being taken when it comes to creating environments that are perceived to be open, or closed, to LGBTQ participants. A grounded theory–based process of data collection and analysis resulted in emergent themes. These themes included (a) "I am not an expert but…, " (b) reactive programming and management, (c) inclusion as a general practice, and (d) the importance of gender-inclusive practices. Management strategies and implications for campus recreation aquatic managers around these emergent themes are discussed regarding the creating of inclusive environments for LGBTQ participants.